Antibiotic Resistance And Plasmid Profiling Of Escherichia Coli Species Isolated From Soil - Norzanora Azlina, A. Samad (Universiti Malaysia Sarawak, (UNIMAS), 2004)
A total of 40 Escherichia coli strains were identified from cattle waste and forest soil (without cattle wastes). All the 40 isolates were confirmed as Gram -negative using gram stain and biochemical test. Most of the isolates were resistant the antibiotics. Bacitracin (90%), Cephalothin (72.5 %) and Erythromycin (85 %). Escherichia coli isolate harboured plasmid ranging from 5.2 tb to 54 kb. One isolate did not display any existence of plasmid (TB15). One strain (TL18) displayed two bands of plasmid with multiple resistant towards the antibiotics tested. This indicates no clear correlation between the antibiotic resistance pattern and the plasmid profile of £. coli isolated from different source of soil.